Discovery and bio‐optimization of human antibody therapeutics using the XenoMouse® transgenic mouse platform. Issue 1 (March 2016) - Foltz, Ian N.; Gunasekaran, Kannan; King, Chadwick T.
Summary: Since the late 1990s, the use of transgenic animal platforms has transformed the discovery of fully human therapeutic monoclonal antibodies. The first approved therapy derived from a transgenic platform – the epidermal growth factor receptor antagonist panitumumab to treat advanced colorectal cancer – was developed using XenoMouse ® technology. Since its approval in 2006, the science of discovering and developing therapeutic monoclonal antibodies derived from the XenoMouse ® platform has advanced considerably. The emerging array of antibody therapeutics developed using transgenic technologies is expected to include antibodies and antibody fragments with novel mechanisms of action and extreme potencies. In addition to these impressive functional properties, these antibodies will be designed to have superior biophysical properties that enable highly efficient large‐scale manufacturing methods. Achieving these new heights in antibody drug discovery will ultimately bring better medicines to patients. Here, we review best practices for the discovery and bio‐optimization of monoclonal antibodies that fit functional design goals and meet high manufacturing standards.